2016
DOI: 10.1111/geb.12545
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 318 continental‐scale species distribution models over a 60‐year prediction horizon: what factors influence the reliability of predictions?

Abstract: Aim Species distribution models (SDMs) are currently the most widely used tools in ecology for evaluating the suitability of environments for biodiversity in the face of future environmental change. In this study we seek to provide an assessment of the predictive performance of SDMs over time. How well do SDMs predict for future time periods and what factors influence predictive performance? Innovation We used a historical spatially explicit database of 1.8 million occurrence records for 318 tetrapod species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 60 publications
2
87
0
1
Order By: Relevance
“…Some species with widely distributed recorded locations had poorer model fits than species with restricted ranges, perhaps reflecting the cosmopolitan distribution of the former (e.g., moderate explained deviance and AUC scores for killer whale and bottlenose dolphin) and the more aggregated nature of others for the latter (e.g., high explained deviance and AUC scores for Māui dolphin, Hector's dolphin). Evidence from previous studies have indicated that species with limited geographic ranges and/or environmental tolerances are generally better modelled than those with greater ranges (Morán‐Ordóñez, Lahoz‐Monfort, Elith, & Wintle, ; Stephenson et al, ; Thomson et al, ) because widespread species are less likely to have sharp easily identifiable environmental thresholds that clearly delineate their environmental niche (Morán‐Ordóñez et al, ). For species with limited ranges, the best model fits were commonly located closer to shore where sampling effort was highest.…”
Section: Discussionmentioning
confidence: 99%
“…Some species with widely distributed recorded locations had poorer model fits than species with restricted ranges, perhaps reflecting the cosmopolitan distribution of the former (e.g., moderate explained deviance and AUC scores for killer whale and bottlenose dolphin) and the more aggregated nature of others for the latter (e.g., high explained deviance and AUC scores for Māui dolphin, Hector's dolphin). Evidence from previous studies have indicated that species with limited geographic ranges and/or environmental tolerances are generally better modelled than those with greater ranges (Morán‐Ordóñez, Lahoz‐Monfort, Elith, & Wintle, ; Stephenson et al, ; Thomson et al, ) because widespread species are less likely to have sharp easily identifiable environmental thresholds that clearly delineate their environmental niche (Morán‐Ordóñez et al, ). For species with limited ranges, the best model fits were commonly located closer to shore where sampling effort was highest.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive performance was assessed in terms of discrimination ability measured using the area under the receiver-operator characteristic curve (AUC; Hanley and McNeil 1982) adapted for use with presence-background samples (Phillips et al 2006). This metric is suited to presence-background data, since calibration cannot be assessed and applying thresholds to predictions loses information (Guillera-Arroita et al 2015, Morán-Ordóñez et al 2016. We calculated AUC using the ten-fold cross-validation provided in Maxent.…”
Section: Modelling Frameworkmentioning
confidence: 99%
“…SDMs are a widely used tool for predicting species distributions in response to changing climate (Engler et al, 2011;Hof, Araújo, Jetz, & Rahbek, 2011;Hof et al, 2018; Morán-Ordóñez, Lahoz-Monfort, Elith, Wintle, & Guisan, 2017;Peterson et al, 2002;Thuiller, Guéguen, Renaud, Karger, & Zimmermann, 2019;Zurell, Graham, Gallien, Thuiller, & Zimmermann, 2018). SDMs are based on statistical correlations between species occurrences and environmental predictor variables (Elith & Leathwick, 2009;Guisan & Thuiller, 2005;Guisan & Zimmermann, 2000), which can then be transferred into future time periods to predict future species distributions under climate change.…”
Section: Introductionmentioning
confidence: 99%